Watriquet de Couvin: dal trattato alla scuola, dal «clerc» al «maître» (Carte Romanze, 2025)
This study proposes a new critical edition of the Dit de l’escole d’amours by Watriquet de Couvin, exploring its role within the medieval didactic tradition. This text diverges from the traités d’amour in verse of the late 13th century, aiming at building a lyric-argumentative text with an edifying purpose. Through intertextual dialogue with Jean de Meun’s Roman de la Rose, Watriquet shapes a discourse on love as a vehicle for ethical and moral transmission.
Keywords: Watriquet de Couvin; dits; Didactic tradition; love treatise; French Middle-Ages